Linking oil platforms and natural reefs: insights into mobile epifauna dynamics - Naeem Abdulaziz Aziz; Rodrigo Riera; Mohammed AlDibis; Radhouane Ben-Hamadou; Pedro Range (Frontiers in Marine Science)
IntroductionArtificial substrates are increasingly employed in marine ecosystems to support benthic communities by providing habitat and enhancing biodiversity, particularly in areas where natural substrates are limited. Understanding the ecological role of these structures is essential for conservation and management, especially in regions undergoing industrial development, such as offshore oil and gas areas.Materials and methodsTo investigate the vertical distribution of mobile epifaunal assemblages, stainless-steel settlement plates were deployed across depths ranging from 10 to 44 meters for a duration of 13 months. The study was conducted between the Al Shaheen Oil Platforms and nearby offshore natural reefs within the Qatari Exclusive Economic Zone (EEZ).ResultsThe survey recorded a total of 2,302 individuals from 42 operational taxonomic units (OTUs), including the first documented presence of Galathea sp. in Qatari waters. Distinct patterns of species distribution were observed, with polyclads and sipunculids predominantly occurring in shallow waters, while deeper sections showed reduced abundance, diversity, and biomass. Although no significant horizontal patterns were detected between reef sites, strong ecological connectivity was evident, indicating that the artificial substrates acted as effective "stepping stones" for mobile fauna.DiscussionThe dominant functional groups included surface deposit feeders (sipunculids), carnivorous flatworms, and polychaetes. Notable depth-related associations were found, such as sipunculids and flatworms with sessile bivalves in shallow areas, and crabs with dead barnacles at deeper depths. These findings provide valuable baseline data on mobile benthic communities inhabiting offshore artificial reefs and highlight their role in promoting biodiversity and connectivity between natural reef habitats. The study also offers important implications for the design, commissioning, and decommissioning of oil and gas infrastructure, with relevance to reef restoration and fisheries enhancement strategies in the region.